A Companion to Medieval Canonization Processes : New Contexts, Perspectives, and Comparisons - Katajala-Peltomaa, Sari (Brill's Companions to the Christian Tradition, 2025)
Canonizations, which officially proclaimed a person's sanctity, were complex, embracing theological, judicial, social, and cultural aspects of medieval Christianity. The dossiers manifest the theological ponderings while also revealing the devotional practices, daily life, and troubles of those not learned in canon law or theology. This volume offers tools for comprehending canonization processes by investigating their judicial background and structural elements, as well as devotional aspects reflected in the depositions. It approaches canonization processes in a three-fold way: as a phenomenon of the past, as a source material with methodological challenges, and as a specific field of historical studies. Furthermore, this volume engages in innovative methodological discussions and illuminates the state-of-the-art and topical new themes. Contributors include: Christian Krötzl, Maria Teresa Fattori, Didier Lett, Saku Pihko, Jenni Kuuliala, Nicole Archambeau, Adelheid Russenberger, Jyrki Nissi, Laura Ackerman Smoller, Sari Katajala-Peltomaa, Marika Räsänen, and Jonathan Greenwood.